Research on Export Competitiveness in Poland Using the Adjusted Revealed Comparative Advantage Index - Salamaga, Marcin (Krakow Review of Economics and Management/Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie, 2015)
The Balassa index (Revealed Comparative Advantage Index - RCA index) is used to estimate a country's export attractiveness and comparative advantage by industry sectors or commodity groups. Because it ranges from 0 to ∞, the measure has many drawbacks. Its empirical distribution is strongly asymmetric and is not stable in time. The Revealed Comparative Advantage Index distribution is strongly dependent on the number of reference countries, industries and commodity groups. As a result, some parameters of the RCA index distribution are not stable. These problematic properties render its outcomes incomparable across time and space. The paper proposes a transformation of the RCA index measure into a new index ranging from -1 to 1 by using a special class of rational functions. The new measure has a symmetric distribution with a stable mean and is independent of industry sectors and commodity groups. The adjusted Revealed Comparative Index was used to research export competitiveness in Poland as compared with Germany. The article compares the stability of the empirical distribution of the Adjusted Revealed Comparative Index and Balassa index across time and according to commodity groups. The data used come from Eurostat on Polish and German export and import commodities by Standard International Trade Classification (SITC) in 2005-2009.